Romania : Fourth Review Under the Stand-By Arrangement and Request for Modification of Performance Criteria: Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Romania. (IMF Staff Country Reports; Country Report, 2012)
This paper discusses Romania's fourth review under the Stand-By Arrangement and request for modification of performance criteria. The authorities are treating the arrangement as precautionary. Additional funds under the program are provided by the European Union. The economy grew by 2.5 percent in 2011, driven by an exceptional agricultural harvest and strong industrial output growth. Domestic demand strengthened as construction and retail sales started to recover, fuelled by higher real disposable incomes.